'They Cannot Herd a Sheep' Populist Politics and Its Struggles for and Against Education in Turkey. Issue 3 (4th May 2023) - Pinar, Ezgi; Gehring, Axel
ABSTRACT: Instruments of direct suppression and tight control are widely discussed parts of education politics in Turkey. They are often perceived as parts of a wider political struggle that is crucial to produce imaginaries and memories supporting the populist narrative of the ruling AKP. The important role of higher education in the reproduction of a professional labour force does, however, indicate that these instruments cannot be reduced to that function. Ideological objectives and economic interests are often in a contradictory relationship, hindering the AKP's ability to formulate a coherent strategy for higher education. Analysing the contradictions of the AKP's higher education policies offers significant insights into the limits of populist politics that are in conflict with aspects of the economic order.